Trajetórias, memórias e experiências dos trabalhadores rurais do projeto Jaíba, M.G. - Moura, Auricharme Cardoso de (2014)
This study aims to understand the lifestyle and struggle of small scale farmers in the Jaíba project, within the most irrigated perimeter in Latin America and located in the extreme north of Minas Gerais covering the municipalities of Jaíba and Matias Cardoso. The Jaíba project is included in the national agricultural context of frontier expansion and reproduction of capitalism in an area sponsored by the state during the twentieth century, thus transforming the ways of working, producing and living for family farming. When discussing the replacement of agricultural subsistence with market agriculture, the plea is focused on the trajectory, the memories and the experience of the men and women in the struggle to have, and remain on the land involved in a dispute over values and space. In more than observing the irrigated perimeter through phrases of effect, and the rural workers as the labor force and/or elements in production, this dissertation seeks to verify how the social and productive relations are constructed within, and outside the territories where notions of rights and citizenship are always punctual.